High Blood Glucose Levels Are Associated with Delayed Postoperative Wound Healing in Patients with Diabetes Mellitus - Hermansyah Hermansyah; Helly Susanti (Journal Keperawatan, 2026)
Background: Diabetes Mellitus (DM) is a chronic metabolic disease that increases the risk of postoperative complications, including delayed wound healing, surgical site infection (SSI), wound dehiscence, and prolonged hospitalization. Hyperglycemia impairs leukocyte function, angiogenesis, collagen synthesis, and tissue regeneration, thereby delaying the wound healing process. The high number of postoperative patients with comorbid Diabetes Mellitus at Meuraxa Regional General Hospital, Banda Aceh, highlights the importance of identifying factors associated with postoperative wound healing. Purpose: To analyze the relationship between blood glucose levels and postoperative wound healing among patients with comorbid Diabetes Mellitus. Methods: This analytical observational study employed a cross-sectional design involving 60 postoperative patients with comorbid Diabetes Mellitus who were selected using an accidental sampling technique between 17 May and 15 June 2025. Blood glucose levels were measured using a calibrated glucometer, while wound healing was assessed using the Bates–Jensen Wound Assessment Tool (BWAT) during a single postoperative wound evaluation. Data were analyzed using the Chi-square test, and the strength of the association was expressed as the Odds Ratio (OR) with a 95% Confidence Interval (CI). Results: A significant association was found between blood glucose levels and postoperative wound healing (p = 0.001). Patients with blood glucose levels ≥180 mg/dL were 28.75 times more likely to experience delayed wound healing than those with blood glucose levels of <180 mg/dL (OR = 28.75; 95% CI: 2.96–279.56), indicating that poor glycemic control is strongly associated with impaired postoperative wound healing. Conclusion: High blood glucose levels are significantly associated with delayed postoperative wound healing in patients with diabetes mellitus. Glycemic control through blood glucose monitoring, patient education, therapy adherence, and multidisciplinary collaboration need to be integrated into perioperative management to accelerate wound healing and reduce postoperative complications.